Pengembangan Prototipe Aplikasi Mobile Untuk Pengelolaan Perjalanan Dinas Berbasis Design Thinking - Ichram Agung Saptowo; Reny Nadlifatin (Jurnal Pendidikan Indonesia, 2025)
Business travel is an integral part of a company’s operations that ensures smooth workflow and supports organizational objectives. However, the management of business travel at PT XYZ, which currently relies on manual processes, often leads to inefficiencies and administrative challenges. With thousands of employees spread across Indonesia, PT XYZ faces significant obstacles in ensuring an effective and efficient travel management system. This study aims to develop a mobile-based travel management application that supports the company’s digital transformation efforts, particularly in human capital management. The development process adopts the Design Thinking approach to deeply understand user needs through five stages: empathize, define, ideate, prototype, and test. Additionally, the Agile Scrum methodology is applied as a collaborative and iterative framework to guide the application development process. The research was conducted between April and June 2025, involving PT XYZ employees who frequently utilize the business travel service. The outcome of this study is a prototype application that automates the end-to-end travel process — from travel request and approval to execution and reporting — and is integrated in real-time with the company's information systems. The feature validation results show that all functional components of the application are considered ready for use, with an average usability score of 8.42, and a visual design quality score of 8.52 (on a scale of 1–10). In addition, the prototype achieved an average score of 81.63 based on Maze testing. Through the combined use of Design Thinking and Agile Scrum, this study delivers tangible contributions to improving efficiency, data accuracy, and transparency in managing business travel. The proposed application is expected to serve as a strategic solution for enhancing travel administration and supporting the digital transformation of human resource processes at PT XYZ. Moreover, the findings from this research offer a practical implementation model for human-centered digital innovation in corporate settings.